Research methodologies, innovations, and philosophies in software systems engineering and information systems - Mora, Manuel, 1961-.; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2012)
'This book aims to advance scientific knowledge on research approaches used in systems engineering, software engineering, and information systems and to update,integrate, disperse and valuable knowledge on research approaches'-- Provided by publisher.
13. Using grounded theory coding mechanisms to analyze case study and focus group data in the context of software process research / Rory O'Connor -- 14. A practical approach to theory structuring and analysis: a way to structure research and perform sub-problem solving in a changing IS landscape / T. Schwartzel and M. M. Eloff -- 15. Integrating conceptual and empirical approaches for software engineering research / Annette Lerine Steenkamp and Theresa Kraft -- 16. Visualization and analysis of frames in collections of messages: content analysis and the measurement of meaning / Esther Vlieger and Loet Leydesdorff -- 17. System approach to MIS and DSS and its modeling within SD / Miroljub Kljajic ... [et al.] -- 18. Project contexts and the possibilities for mixing software development and systems approaches / D. Petkov ... [et al.] -- 19. Selecting strategies and approaches in systems engineering: applying the descriptive research method / Moti Frank -- 20. Engineering design as research / Timothy L.J. Ferris -- 21. Validation and design science research in information systems / Rafael A. Gonzalez and Henk G. Sol.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed January 23, 2012).
Keywords: Software engineering; System engineering; Research -- Methodology; Information technology; Critical realism; Formal ontologies; Interpretative information systems research; Organizational knowledge; Process theory; Relevance in information systems research; Semantic map; Software engineering research; Software process research; Structural equation modeling